Construction and application of pancreatic exocrine organoid and spheroid for drug screening and precision medicine - Tan, Xin; Huang, Bangwei; Yang, Xinyi; Wang, Pengyuan; Hu, Lianghao (Frontiers in Cell and Developmental Biology, 2026)
The incidence of pancreatic exocrine disorders, particularly pancreatic cancer, has been steadily rising. However, treatment options remain limited, with substantial interindividual variability in therapeutic efficacy. This clinical challenge has accelerated the development of advanced three-dimensional (3D) modeling systems, with patient-derived organoids and multicellular spheroids emerging as transformative tools that faithfully recapitulate tumor pathophysiology. In contrast to 2D cultures, which fail to recapitulate the three-dimensional spatial architecture and cell-cell interactions found in vivo, these models have gained prominence in pancreatic cancer research due to their unique capacity to: (1) precisely mimic the tumor microenvironment (TME), (2) preserve tumor heterogeneity, and (3) enable rapid establishment. This review systematically examines current methodologies for constructing pancreatic exocrine 3D models, their integration with bioengineering platforms for drug screening, and innovative applications in multi-omics-driven precision medicine. We further evaluate the translational potential of these systems in clinical decision-making and discuss how they may reshape therapeutic paradigms for pancreatic diseases, offering new avenues for personalized treatment strategies.